LEGAL PROTECTION OF STEAM ACCOUNT OWNERSHIP AS VIRTUAL PROPERTY REVIEWED FROM OBJECTIVE LAW IN INDONESIA - Nurdhito, Dicho Sigit (Zhata Institut, 2024)
Humans in their lives need objects to be used directly or as tools to meet their daily needs. The progress of the technological era with the emergence of the internet also has an impact on changes not only on the systematic side but also affects the objects. The legal symptom is that media on objects in the Civil Code is the real world, while virtual property media is the world of the internet or cyber world. The phenomenon of the concept of virtual property in the future will increasingly occur in human life and even become an integral part of human life. In this research, it was carried out in a normative juridical manner. the approach is carried out with a statutory and contextual approach. Data sources come from three sources, namely primary which are invitation laws, secondary which are books and scientific papers, tertiary which are dictionaries and encyclopedias. Data collection was carried out by means of a literature study. Data analysis was carried out using descriptive-qualitative. The results of this study indicate that STEAM accounts are part of assets in the form of virtual property which are intangible objects in the Civil Code because they fulfill the elements of objects in general. A STEAM account can be attached with ownership rights in the form of property rights and proof of ownership of intangible objects in article 613 as evidenced by an authentic deed or private agreement, a STEAM account as a substitute for an underhand agreement, namely verification of the account with the email address and telephone number of the account owner . At this time the STEAM platform has been registered as an electronic system operator (PSE), so all acts of cybercrime are directly protected by provisions relating to information and electronic transactions and policies from the STEAM platform, this is part of protection and legal certainty.